Through A Xenophobic Lens: Degeneration Theory in W. Christy Cabanne’s Martyrs of the Alamo - Savage Lee, Susan; Csabafi, Tamas Z. (Hungarian Journal of English and American Studies, 2021)
At the turn of the twentieth century, social theories developed in both the U.S. and Europe suggested that those at the top, or those most well endowed with good genetics, would stay that way, while those with poor genetics had little hope of changing their circumstances.  Degeneration theory, as this concept was called when it took root in the United States from the late 1890s, before it had evolved to formally become eugenics in the 1910s, and beyond. While eugenics offices opened in Berlin in 1905, in England in 1907-08, and in the United States in 1910, there were many forms of it, including degeneration theory. What bound all the theories together was the notion of biology and heredity.            Westerns like Martyrs of the Alamo became a vehicle to explore these concerns because they inundated everyday Americans with illustrations of national identity. Films like these often mixed fantasy with ideology. This is clearly evident in W. Christy Cabanne’s anti-Mexican sentiment in Martyrs of the Alamo. Examining Cabanne’s film through the lens of degeneracy theory provides a greater understanding of American social concerns in the 1910s. These concerns, characterized by xenophobic depictions of immigrants, particularly Mexicans, culminated in the linking of immigrant bodies and disease with heredity and genetics, namely through theories of degeneration . Cabanne’s Martyrs of the Alamo suggests, through the reproduction of the conflict surrounding the Alamo Mission, that the alternative to “race suicide” is a fantasy of American heroism, collectivism, and cultural exclusion. (SS and TZCS)